Occupational Stress and Quality of Life in Nursing - Silva, Aline Moraes da; Guimarães, Liliana Andolpho Magalhães (Paidéia (Ribeirão Preto), 2016)
To reduce the work related to stress and the psychosocial risk is not only an imperative question, but also moral. This epistemological study aims to verify the presence of the occupational stress and quality of life related to health in nursing professionals. We used three questionnaires: (a) Socio Demographic Questionnaire, (b) Job Strain Scale, and (c) Item Short Form Health Survey. Statistical analysis was performed between the questionnaires, analysis of variance (ANOVA) and simple and multiple linear regression. It was found that 60.8% of the participants see the high demand of work, 71.8% high control on the developed activity and 85.5% low social support. Related to eight dominant of quality of life, the most damaged are: pain (µ = 61.87) and vitality (µ = 62.25). It was concluded that although in most sample experiences an intermediary risk situation to stress, the quality of life showed a damaged.